Symbols of defeat in the construction of national identity - Mock, Steven J. (Cambridge University Press, 2012)
"THis is the first book to camparatively examine nations that emphasize images of their own defeat in their mythology and sense of history. Cases include Serbia, Israel, France, Greece and Ghana. Through exploring this phenomenon, it offers new insights into current theories in the study of nations and nationalism, incorporating approaches from diverse disciplines such as sociology, anthropology and the psychology of religion"--